Polemika z Żydami i judaizmem w "Ad Quirinum" (liber primus) Cypriana z Kartaginy - Misiarczyk, Leszek (Vox Patrum, 2019)
The article presents a short description of the text as a collection of biblical quotes focused on such topics as the Mosaic Law (Book I), Christology (Book II) and Christian virtues (Book III) and also comments on the version of the biblical text that Cyprian cites. A survey of comparative studies showed that the biblical text cited by Cyprian departs from the Hieronim Vulgate. Secondly, Cyprian’s writing is an autonomous treatise independent of Adversus Iudaeos Tertullian, written at the request of Quirinius, who aimed to provide the addressee and other Christians in Carthage tools in the form of biblical passages to fight the growing Jewish proselytism. As for the historical context of its creation, the treaty is part of the middle of the third century. Previous good relations between Christians and Jews in North Africa, as evidenced by even Jewish necropolises with Christian graves or inscriptions with a cross and a menorah, are beginning to break due to the growing Jewish proselytism and the growth of the Christian community.